Respuesta :

Answer:

A. One solution

Step-by-step explanation:

6 + x/5 = x/5 - 5 - 3x/10

Cancel equal terms on both sides.

6=-5-3x/10

Multiply both sides of the equation by 10.

60=-50-3x

Move the variable to the left-hand side and change the sign.

60+3x=-50

Move the constant to the right-hand side and change the sign.

3x=-50-60

Calculate the difference.

3x=-110

Divide both sides by 3.

x=-110/3

=-36 2/3

Meaning one solution.

Hope this helps :)

Answer:

The answer you are looking for is A